Social organization in three Philippine villages explorations in rural anthropology - Jocano, Felipe Landa 1930- (Research and Development Center, Centro Escolar University, 1988)
"This small volume is a comparative ethnography of rural life in selected villages located in different places in the Philippines: Ilocos, Tagalog and Bisayas. Our purpose in doing this is to identify the commonly shared social and cultural patterns of behavior, values, and institutions among Filipinos, in spite of geographical distances that separate these villages. So much has been written about the ethnic differences among Filipinos. This emphasis on differences has so far been divisive and has given rise to an orientation that has influenced many Filipinos to think not in terms of national unity but in terms of ethnic display."--Objectives of the study, p. 1.